PENGARUH KOMPENSASI, KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA NON FISIK TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI BERPRESTASI SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan Divisi Operation & Maintenance PT. Purna Baja Harsco) - Subarkah, Ridwan; Kambara, Roni; Ichwannudin, Wawan (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2017)
The purpose of this research to know influence compensation, non physical working area, transformational leadership to employee performance with achievement motivation as intervening variable. Independent variable in this research are compensation (X3), non physical working area (X2), transformational leadership (X1), intervening and dependent variable is achievement motivation, dependent variabel is employee performance. This research is held in Operation & Maintenance Division PT Purna Baja Harsco Cilegon Banten. Sample are 129 respondents. The primary data were collected using a quesionnaire that consist of statement list and analyzed with SEM (Structural Equation Modeling) with help of  SmartPLS statistics software. Seven hypotheses contructed in this research there were five hyphotheses are accepted, Compensation is influential positive and significant on employees performance(1). Compensation is influential positive and significant on achievement motivation(2). Non physical working area is influential positive and significant on employees performance(3). Non physical working area s influential positive and significant on achievement motivation(4). Achievement motivation is influential positive and significant on employees performance(5). While two others hypotheses is rejected, Transformational Leadership is influential positive but not significant on employees performance(1). Transformational Leadership is influential positive but not significant on achievement motivation(2).The largest constribution to Employee Performace comes from Non physical working area.